Theoretical Mechanisms, Practice Foundations, and Policy Options for Big Data Driven High-quality Economic Growth in China - Li Hui (Contemporary Social Sciences, 2020)
In the transition of China’s economy from high-speed growth to high-quality growth in the new era, economic practices are oriented to fostering new growth drivers, developing new industries, and forming new models. Based on the data flow, big data effectively integrates technology, material, fund, and human resource flows and reveals new paths for the development of new growth drivers, new industries and new models. Adopting an analytical framework with “macro－meso－micro” levels, this paper elaborates on the theoretical mechanisms by which big data drives high-quality growth through efficiency improvements, upgrades of industrial structures, and business model innovations. It also explores the practical foundations for big data driven high-quality growth including technological advancements of big data, the development of big data industries, and the formulation of big data strategies. Finally, this paper proposes policy options for big data promoting high-quality growth in terms of developing digital economy, consolidating the infrastructure construction of big data, expediting convergence of big data and the real economy, advocating for a big data culture, and expanding financing options for big data